Cardiac autonomic and physiological responses to hypoxic exercise of different intensities - Fornasiero, A.; Skafidas, S.; Stella, F.; Zignoli, A.; Savoldelli, A.; Bortolan, L.; Rakobowchuk, M.; Pellegrini, B.; Schena, F.; Mourot, L. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Hypoxic exercise (i.e. exercise under reduced oxygen availability) has been shown to represent a valid alternative to normoxic exercise to provide an adequate training stimulus, promoting beneficial physiological training adaptations as well as positive health-related outcomes. Nowadays, hypoxic exercise of various intensities is implemented within the training programs of different athletic and special populations. Different types of high-intensity hypoxic exercise are commonly employed to maximize the performance enhancement in athletes involved in endurance and intermittent sports, whilst moderate-intensity hypoxic exercise is adopted to increase the physiological load while reducing the mechanical load both in obese and geriatric patients, as well as a therapeutic tool for weight loss and type 2 diabetes prevention. Both at maximal and sub-maximal exercise intensities, acute hypoxic exercise can result in markedly altered cardiac, ventilatory and metabolic responses, which may lead to increased exercise-induced homeostatic perturbation, greater autonomic disturbance and delayed postexercise cardiac autonomic recovery. Some of these aspects must be carefully considered when prescribing hypoxic exercise. The purpose of this presentation is to examine the exercise and recovery physiological and cardiac autonomic responses to 1) a maximal hypoxic exercise and 2) to sub-maximal hypoxic exercises performed at the same absolute (based on mechanical load) or same relative (based on heart rate) normoxic exercise intensity. Current evidence suggests that increased exercise-induced homeostatic perturbation and delayed cardiac autonomic recovery mainly occur in response to maximal hypoxic exercise and sub-maximal hypoxic exercise performed at the same absolute normoxic exercise intensity. Differently, when performed at the same relative normoxic exercise intensity (based on heart rate) hypoxic exercise triggers similar cardiac autonomic and physiological responses to normoxic exercise, with a reduced mechanical load.